Laura. La dodecafonia di Luigi Dallapiccola dietro le quinte - Ruffini, Mario (Libere carte, 2018)
Discovering Laura Coen Luzzatto means getting to the core of the musical history of the Italian 20th century, the backstage of the complex dodecaphonic crossing made by Luigi Dallapiccola; it means shedding light on the woman who illuminated the composer's path amidst the dramas of the century. Laura met Luigi in Florence in 1931, and devoted herself to him and his art since then. They married in 1938, and she became Laura Dallapiccola. She was an atheist, born in Trieste in a Jewish family, whereas he was Istrian-born and a doubtful Catholic. They both arrived in Florence following Dante's myth, and immediately connected thanks to Laura's degree dissertation (which is deservingly brought to light in this volume by the University of Florence, where she discussed it in 1932) and to their shared belief that both their birthplaces, despite being borderlands, were of Italian nationality. From that moment onwards, thanks to her, the composer's story opened to European culture, to Joyce, Proust, Mann and, again thanks to her, the Dallapiccola dodecaphony becomes rooted in the vocal style of the Italian culture, thus differentiating itself from the Viennese dodecaphony. Laura, then, to better discover Luigi Dallapiccola and to look at the 20th century with new eyes.